Work in transition : cultural capital and highly skilled migrants' passages into the labour market - Nohl, Arnd-Michael; Schittenhelm, Karin, 1957-; Schmidtke, Oliver; Weiss, Anja (University of Toronto Press, 2014)
"Despite the fact that many countries target highly skilled migrants for recruitment in the global labour market, few of those migrants are able to take full advantage of their educational and professional qualifications in their new homes. Work in Transition examines this paradox, using extended narrative interviews that focus on the role that cultural capital plays in the labour market. Comparing the migrant experience in Germany, Canada, and Turkey, Work in Transition shows how migrants develop their cultural capital in order to enter the workforce, as well as how failure to leverage that capital can lead to permanent exclusion from professional positions. Exposing the mechanisms that drive inclusion and exclusion for migrants from a transatlantic comparative perspective, this book provides a unique analytical approach to an increasingly important global issue."--